ANALISIS PENGARUH THE FED RATE, INDEKS DOW JONES DAN INDEKS NIKKEI225 TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA (BEI) PERIODE 2008-2013 - Hotneri Gom Gom (Departemen Ekonomi Pembangunan USU, 2013)
This research is addressed to determine the influencesof The Fed, Indeks Dow Jones, and Nikkei 225 against IHSG in Bursa Efek Indonesia (BEI) for a period of 2008-2013. The data type used in this research is Time Series in the form of the Fed Rate, Indeks Dow Jones, Indeks Nikkei225 and Indeks Harga SahamGabungan (IHSG) data during January 2008 until November 2013.The Analytical Technique that used to conduct the analysis is Vector Auto Regression (VAR), at significant level 5%, by using computer application program aid Eviws 7.0.The output of this research indicates that the Fed variable influences negatively against the IHSG, while Index Dow Jones and Index Nikkei225 influence positively against the IHSG.Keyword: IHSG, The Fed, Indeks Dow Jones, Indeks Nikkei 225, VAR